The association of the intima-media thickness of common carotid artery with coronary artery disease - Tariq Hussien, Alrahomi (2008)
Topic: The association between intima-media thickness of the common carotid artery with coronary artery disease. Background: Coronary artery disease (CAD) occurs due to coronary artery stenosis secondary to atherosclerosis. CAD presents differently ranges from silent preclinical stage to sudden acute myocardial infraction or sudden death. CAD is one of the most common diseases in the world and in Malaysia it is considered the number one killer. Common carotid arteries provide a 11window" to the coronary arteries as both have similar risk factors. Thus, carotid atherosclerosis provide a window to the degree of coronary atherosclerosis in an individual by examining the carotid artery wall using a highresolution B-mode ultrasound transducer to measure the carotid IMT (CIMT). Objecth'es: 1- To demonstrate if there is any association between the increase in the CIMT and CAD. 2. To study whether CIMT can be used as a surrogate marker of CAD. Methodology: High resolution B mode ultrasound examination of both common carotid arteries was performed on 113 male patients with suspected CAD. CIMT were measured thre~ times from the distal I em of each common carotid artery. Thereafter, the coronary angiography was done on the next day. Data about the traditional risk factors of CAD as age, body mass index (BMI), hypertension, diabetes mellitus, hyperlipidaemia and smoking were collected. XVI Results: It was found that CIMT was significantly higher in patients with CAD confirmed angiographically than in patients with normal coronary arteries (p~value < 0.001) and CIMT values were higher in patients with advanced CAD (three vessels CAD compared with one and two vessels CAD) (p-value < 0.001). The mean CIMT in patients without CAD was 0.72mm, in one vessel CAD was 0.87mm, in two vessels CAD was 0.93 mm and in three vessels CAD was l.lmm. The sensitivity and specificity ofCIMT were 81.3% and 81.8% respectively while PPV and NPV came out to be 94.9% and 51.5% respectively. In this study, the cardiovascular risk factors and their relation to CAD and CIMT revealed a significant association between age, smoking, DM and hyperlipidaemia with CAD and significant association was found between age, smoking and DM with increased CIMT (with p~value < 0.05). Conclusion: The results of this study demonstrated that CIMT was significantly higher in patients with CAD especially in patients with advanced CAD. High resolution B~mode ultrasound measurement of CIMT can be used clinically as screening tool for early detection of patients with suspected CAD with no history of myocardial infarction or patients who are free of symptoms but with a number of cardiovascular risk factors.